(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The work deals with the bioethology of Stereonychus fraxini infesting the olive trees in Sicily, observed during 2000-2003. Either in the adult, or in the larval stage, the species prefers to develop on tender leaves, but occasionally may infest also the flowers and the young fruits. Its life-cyele lasts from the ending of March until June. Stereonychus fraxini accomplishes in Sicily one generation per year and its damage must only be related to the young olive plantations, viz. trees below 3-4 years old.